Supermercados, estrategias y pequeños productores hortícolas en el municipio de Acatzingo: el caso Walmart - Diosey Ramón Lugo-Morin (El Colegio Mexiquense, A.C., 2013)
The goal of this paper is to undertake a spatial and comparative analysis of the changes in the forest production in the Eighth Chilean Region based on a Geographic Information System (gis). The forest production is concentrated in the Seventh, Eighth, and Ninth Regions, which account for 76.8% of the planted area. The analysis will be based on spatialized information of the forest production for the Eighth region published in the Agricultural Census in 1997 and 2007. From 1997 to 2007 the forest area presented a strong expansion. This dynamic can bring many changes in the economy and society, and natural environments.